O capital social dos refugiados: bagagem cultural versus políticas públicas - Pacífico, Andrea Maria Calazans Pacheco (2008)
This thesis is a result of an exhausted research about the importance of inserting social capital studies within the refugee issues, by joining the role of the cultural background they bring with them from the country of origin with the public policies adopted by the host place. Secondly, a theoretical investigation on social capital, a construct also used as a public policy tool, was prepared. Its importance is within the relationships produced between locals and foreigners, precisely between refugees and the local community, due to the irreversible migratory phenomena, especially due to the forced migration, as part of the new International Agenda. Thus, it is necessary to get ready the host community and the government to host them, as the integration among them could join efforts to weaken situational problems already rooted in the society, as lack of trust in the community and in the public institutions, which lead to the lack of civic participation, of cooperation and of support to host society and to refugees development. Ab initio, this work deals with the refugee s juridical definition, created by the beginning of the cold war, under political causes and aims, and based on that society, being necessary changes to adjust it to the new international system, which is characterized by human rights organizations strength. A posteriori, there is an evaluation on policies targeted on these people, in Brazil and in Canada, after characterizing these societies, qualified by the myths of tender society (the Brazilian one) and multiculturalism (the Canadian one), although, when dealing with refugees, these myths stay in theory, not reaching the practice, as wished. The originality of this research is the evaluation of the social capital produced by refugees in São Paulo and in Toronto, the role of some supporting networks and their integration as well as whether or not the refugees feel themselves as citizens and whether or not they are seen like that by the host society. At the end of the day, the importance of the cultural background the refugees bring from the country of origin and the influence of the public policy adopted within both cities were examined. Comparison, which is common in migration studies, and transdisciplinarity were the approaches chosen, as there is no single science which is able to solve the refugee dilemma